Histological Studies on the Duodenum of the Guinea Pig (Cavia porcellus) in Postnatal Age Groups - K. Raja (Indian Journal of Veterinary Anatomy, 2022)
In the present study, the wall of the duodenum of guinea pigs was composed of four layers namely tunica mucosa, tunica submucosa, tunica muscularis and tunica serosa in all the age groups i.e 0-2 weeks to 16-32 weeks–old guinea pigs (n=24). Villi were taller and had a finger like appearance except in 0-2 weeks-old guinea pigs. Surface epithelium was lined by the simple columnar epithelium with few goblet cells, along with this few globular leukocytes and intra epithelial cells were also observed in all the age groups. Enterochromaffin cells were few observed stain at the basal part of the crypts and less in the surface epithelium. Lamina propria was composed of loose connective tissue. Crypts of Lieberkuhn present throughout the lamina propria. Tunica submucosa comprised of loose connective tissue mainly of collagen and reticular fibres and few elastic fibres in the wall of the blood vessels. Submucosa of the duodenum showed the Brunner’s glands of various sizes. Inner circular and outer longitudinal muscle layers were observed in the tunica muscularis. The mean height and width of the villi, height of the columnar cells and thickness of the tunica muscularis increased as the age advanced in all the age groups.